Prophylactic Vitamin D Prescribing for Adult Inpatients on Psychiatric Wards at Warneford Hospital – an Audit - Justyna Gromala; Sagar Jobanputra (BJPsych Open)
Aims: Vitamin D deficiency is a common and preventable problem seen in the UK, which can contribute to physical and mental health illness. The Department of Health and Social Care states that adults in restricted settings, such as inpatient psychiatric units, are at increased risk of vitamin D deficiency due to limited exposure to sunlight. Local Trust guidelines specify that all adult inpatients should be offered vitamin D prophylaxis year-round, unless there are symptoms of osteomalacia, in which case vitamin D serum levels should be tested and a treatment dose regime prescribed. Despite this, we noted that many patients did not receive prophylactic treatment. The primary aim of this audit was to increase the number of prophylactic vitamin D prescriptions for psychiatric inpatients at Warneford Hospital, in line with local Trust guidelines and national guidance.